Application of PCR markers for detecting 1BL.1RS wheat-rye chromosome translocations and (1B)1R substitutions - Motsny, I.I.; Sudarchuk, L.V.; Galaev, A.V.; Chebotar, S.V. (Фактори експериментальної еволюції організмів, 2014)
Aims. Molecular-genetic and cytological analyses were carried out to detect the alien genes in original introgression stocks and to investigate their inheritance. Methods. Rye (Xrems1303, SR1R003) and wheat (Xgwm18-1BS, Xgwm550-1BS, Xgwm140-1BL, Xgwm153-1BL, Xgwm357-1AL, Taglut-1AS) microsatellites and secalin-specific STS-marker (ω-sec-P3+ ω-sec-P4) have been applied. Results. The (1B)1R wheat-rye chromosome substitution and 1BL.1RS translocation have been identified. The pairing between short arms of the 1BL.1RS translocation and of bread wheat chromosome 1B was observed with very low frequency (in 0.3 % PMCs). Conclusions. The stocks have (1B)1R wheat-rye chromosome substitution or 1BL.1RS translocation. The translocation was contributed by the collection strains, derived from wheat cv. Avrora and originated from Petkus rye. The intact rye chromosome 1R for the substitution was contributed by triticale (8x) cv. AD825 and originated from rye Voronezhskaya SHI. The substitution stocks were susceptible to leaf and stem rusts because of another origination of the 1R chromosome. Three major linked genes determining hairiness of the leaf upper surface (Hlup), lower surface (Hllow) and leaf margin (Hlm) were revealed. The genes were contributed by a synthetic (T. timopheevii/Ae. tauschii) and were non-allelic to Hl1 gene.

Key words: Triticum aestivum, (1B)1R substitution, 1BL.1RS translocation, hairy leaf, PCR-markers.